Antibiotic sensitivity pattern of gram negative uropathogenic bacilli at a private hospital in Dhaka city - Md. Abdullah Yusuf; Afroza Begum; Chowdhury Rafiqul Ahsan (Al Ameen Medical College, 2015)
Background: Urinary tract infection (UTI) is one of the most common infections affecting different age group of the patients. Objective: The purpose of the present study was to find out the spectrum and antibiotic sensitivity pattern of uropathogens isolated from the UTI patients. Methodology: This retrospective study was conducted at a private clinic in Dhaka city during January to December, 2012 for a period of one year. Urine was collected from suspected cases of UTI patients. Isolation and identification was performed by standard methods. Antibiotic sensitivity and interpretation was done according to CLSI guidelines. Result: A total number of 501 clinical samples of urine were collected of which 141(28.0%) showed significant bacterial growth. The commonest bacterium isolated from the culture positive urine sample was Klebsiella species (41.8%) followed by Escherichia coli (39.7%), Pseudomonas species (15.6%) and Proteus species (2.8%). Members of the Enterobacteriaceae were 80-100% sensitive to imipenem while they were found variably sensitive to other commonly used antibiotics. Sensitivity pattern of Pseudomonas species were also varied. Conclusion: In conclusion Klebsiella species is the most common bacteria causing UTI followed by E. coli with varied sensitivity pattern.